The changing landscape and dynamics of turkey’s political economy in the twenty-first century: An introduction - (:unkn) unknown (Palgrave Macmillan, 2020)
Turkey’s political economy in the 2000s has shown a remarkable diversification in its international political economy landscape, its domestic political economy framework, instrumental alternatives and geographic outreach, despite intensifying internal and external challenges. The overall framework of this book seeks to make a comprehensive analysis of Turkey’s political economy in the twenty-first century and to grasp how it has diversified in the domestic, instrumental and geographic domains. To this end, this introductory chapter will first rethink Turkey’s political economy with an eye to explaining Turkey’s economic growth and political transformation in line with the changes occurring in world economics from the Washington Consensus era to the current “mix” or “hybrid” era encompassing both the characteristics of post-Washington and Beijing Consensus era. In sum, the overarching aim of this book project is twofold: to scrutinize the transformation experienced in Turkey’s political economy in the 2000s and to link this transformation with the changing preferences in Turkish foreign policy. © 2020, The Author(s).
Keywords: Emerging powers and markets; Turkey; Turkey’s international political economy; Turkish foreign policy